Antagonism of Trichoderma harzianum and Trichoderma viride on isolates of Fusarium spp. from Nicotiana tabacum - Ceiro-Catasú, Wilson Geobel; Vega-González, Yusel; Taco-Sánchez, María Eulalia; Gaibor-Fernández, Ramiro Remigio; Sosa-Sánchez, Oandis (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Tobacco production is a key line in the Cuban economy and generates the largest income in the agricultural sector. Within phytopathogens affecting this plant, Fusarium spp., constitutes a pest of interest, due to vascular involvements that cause deterioration of the commercial value of the leaf. Therefore, the research was carried out with the aim of determining the antagonistic activity in vitro of native strains of Trichoderma harzianum and T. viride on isolates of Fusarium oxysporum and F. phyllophylum, from Nicotiana tabacum L. in Granma province, Cuba. The work was carried out at the Laboratory of Agricultural Microbiology, University of Granma. Half dextrose potato agar was prepared to establish the dual crops of Trichoderma spp. vs. Fusarium spp. Once the treatments were established and the incubation time had elapsed, the percentage inhibition of mycelial growth, antagonistic capacity and mycoparasitic activity was determined. A fully randomized design with four replicas per treatment was used and a two factorial ANOVA and Tukey test (p≤0.05) were used for statistical processing. It was shown that the strains of Trichoderma spp., recorded intermediate values of phytopathogenic inhibition, the competitiveness of the antagonist was mostly located in class two of the Bell scale and it was found that penetration, winding, vacuolization, deformation and granulation constitute the main forms of mycoparasitism. Which points to this biocontrol method as an alternative to consider for the management of Fusarium spp., in tobacco agroecosystems.